The automation of data analysis research of color preferences of Antarctic’s winterers - Madyar, S.-A.I.; Kovalevskaya, Ye.Ye.; Globa, L. S.; Shtogrina, Ye. S.; Kosovnenko, R. A.; Dobrov, Yu. A.; Moyseyenko, Ye. V. (Ukrainian Antarctic Journal, 2015)
The article describes the main approaches and technical solutions used in the creation of software tools for the analysis of human color preferences. The techniques of testing, are the main functions of the software analysis tools color preferences, the results of his work and the direction of improvement. Methods of evaluation of the results of preferential chromaticity selection to determine psycho-physiological characteristics of man has passed many years of approbation. The methodology applied in practice for the psychophysiological selection of candidates for the Antarctic expedition, for the psychological support of Antarctic winterers, to facilitate the passage of the process of rehabilitation and adaptation of winterers. The technology is based оn the psychophysiology of color perception and opens up new possibilities for diagnostic of psychophysiological human state and ways of assessment and prediction of adaptive rearrangements of psychophysiological functions for professional medical selection. The method creates an individual approach to the use of color and correction of bioregulation disorders that occur as а result of the different levels of stress including large psycho-emotional stress. То automate the analysis of data color preference survey developed а software tool that allows to increase the efficiency of robots experts NASC and eliminate the subjective factor in determining the color preference аnd interpretation of test results. Further development of software tools is aimed at expanding of the range of functions of diagnostics and analysis of psychophysiological state. These functions will focused оn providing of statistical researches, analysis of the characteristics of sequences of color preferences and comparison them with reference models. For presentation of the results we plan to use graphs, charts and diagrams built automatically in accordance with the criteria defined bу the experts.